Electroconductive Hydrogel Based on Functional Poly(Ethylenedioxy Thiophene) - Mawad, D.; Artzy-Schnirman, A.; Tonkin, J.; Ramos, J.; Inal, S.; Mahat, M.; Darwish, Nadim; Zwi-Dantsis, L.; Malliaras, G.; Gooding, J.; Lauto, A.; Stevens, M. (American Chemical Society, 2016)
© 2016 American Chemical Society. Poly(ethylene dioxythiophene) with functional pendant groups bearing double bonds is synthesized and employed for the fabrication of electroactive hydrogels with advantageous characteristics: covalently cross-linked porous 3D scaffolds with notable swelling ratio, appropriate mechanical properties, electroactivity in physiological conditions, and suitability for proliferation and differentiation of C2C12 cells. This is a new approach for the fabrication of conductive engineered constructs.